Improving Vocational Students’ Competence in ASTM-Based Mechanical Test Specimen Preparation through Intensive Mentoring - Devi Eka Septiyani; Rachmad Imbang Tritjahjono; Destri Muliastri; Sutiana; Ii Wisnu Wasita; Slamet Raharjo (Jurnal Difusi, 2026)
Internship programs (PKL) are crucial tools for aligning Vocational High School (SMK) students’ competencies with the precision industry’s requirements. However, limited school facilities often hinder the mastery of advanced machining techniques, particularly in fabricating components with tight tolerances. This community service activity aims to enhance the technical skills of two machining students through six months of intensive mentoring in a manufacturing laboratory. The method employed was Project-Based Learning (PBL), focusing on the fabrication of tensile and impact test specimens. We collected data through daily mentoring logs, performance observations, and final product evaluations. The results demonstrated a significant improvement in operational independence and measurement precision. The students’ specimens were verified to meet dimensional and surface roughness quality standards in accordance with ASTM protocols. This success proves that a small-ratio mentoring model is effective in transferring specialized machining expertise, ready for mechanical testing based on ASTM standards.